Coping and Religiosity of Polish Breast Cancer Patients - Żołnierz, Joanna (Religions, 2023)
Religiosity can support a patient in coping with a stressful situation such as breast cancer. In this study, the authors aimed to explain the relationships between the religiosity of the respondents and the religious crises they experienced and coping strategies, as well as between coping strategies and the disease duration. The research method used is the method of diagnostic survey, and the tools: a questionnaire of our own, making it possible to determine sociodemographic variables and standardized scales: the Inventory for Measuring Coping with Stress—Mini-COPE (the brief COPE), the Polish Centrality of Religiosity Scale (CRS) and the Religious Crisis Scale by W. Prężyna (RCS). With approval from the Bioethics Committee at the Medical University of Lublin (KE-0254/133/2015), 69 female subjects with breast cancer were studied. The results showed statistically significant positive correlations between the centrality of religiosity and selected components of religiosity and action-oriented coping strategies. RCS scores correlate negatively with more adaptive coping strategies and positively with ineffective ones. Additionally, patients suffering from breast cancer for more than five years, are statistically significantly different from those with shorter disease duration only in their scores for the CRS “public practice” subscale. Mature religiosity promotes the adoption of constructive coping strategies, while religious crisis hinders the process of coping with stressful situations. It appears necessary to integrate spiritual care into the treatment process of cancer patients.